Factors that affect the usage of internet banking in Selangor / Katijah Mohamad Zubir - Mohamad Zubir, Katijah (Faculty of Business and Management, 2015)
Technological developments, specifically in the area of telecommunications and information technology, transform the banking industry. One part of this which is growing rapidly is Internet banking. In Malaysia, the usage of Internet banking, which started about 14 years ago, has been well accepted by consumers. For banking industry, Internet banking acts as a vital strategy for banks and financial institutions to keep customer loyalty and remain competitive. However, several risks arise by using internet can also affect customer’s adoption of Internet banking.